2018
DOI: 10.3390/magnetochemistry4040047
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the pH-Induced Functional Phase Space of Human Serum Albumin by EPR Spectroscopy

Abstract: A systematic study on the self-assembled solution system of human serum albumin (HSA) and paramagnetic doxyl stearic acid (5-DSA and 16-DSA) ligands is reported covering the broad pH range 0.7–12.9, mainly using electron paramagnetic resonance (EPR) methods. It is tested to which extent the pH-induced conformational isomers of HSA reveal themselves in continuous wave (CW) EPR spectra from this spin probing approach in comparison to an established spin-labeling strategy utilizing 3-maleimido proxyl (5-MSL). Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 161 publications
(270 reference statements)
1
41
0
Order By: Relevance
“…Moreover, ethanol above a certain concentration in the sample can cause HSA denaturation . Examining the pH of the samples showed that they all range between pH 7.4 to 8.0, in which HSA is in its native form, so the natural conformation and environment of the protein is completely preserved …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, ethanol above a certain concentration in the sample can cause HSA denaturation . Examining the pH of the samples showed that they all range between pH 7.4 to 8.0, in which HSA is in its native form, so the natural conformation and environment of the protein is completely preserved …”
Section: Methodsmentioning
confidence: 99%
“…Shorter NÀ O bond length and the presence of negative charges close to NO * moiety and the deviation of NÀ O from planarity (the so called out of plane À OOP-angle) can be named as other factors which increase the hyperfine coupling values. [25][26][27][28][29][30][31] At physiological pH, HSA is negatively charged (~19e) [14,32,33] and it is a well-established fact that hydrophilic negative headgroups and hydrophobic moieties are required for binding to the fatty acid binding sites of HSA. The high affinity binding site of FAs to the protein are the ones who have hydrogen bond and /or electrostatic interactions with the ligand carboxylate head group.…”
Section: Comparisons With Purified Hsamentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, this study was inspired by the earliest spin‐labeling experiments on albumin with the 3‐amino‐proxyl, or 3‐maleimido‐proxyl spin labels . However, these reagents typically generate a mixture of lysine‐ and cysteine‐labeled albumins resulting in the emergence of rather unspecific labeling sites . Selective labeling of the highly conserved Cys34 residue in HSA with the cysteine‐specific methanethiosulfonate spin label (MTSSL) was reported earlier, serving as a tool for investigations on e. g. albumin fragment dynamics .…”
Section: Introductionmentioning
confidence: 99%